2010
DOI: 10.1111/j.1524-4725.2010.01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical Transfer Diagnosis of Pigmented Lesions

Abstract: This technology continues to be a promising adjunct to clinical skin cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Preliminary results based on analyses of independent measurements performed on a limited set of suspicious lesions [15,16] indicated that a linear binary classifier would suffice to discriminate between independent measurements on malignant (class 1) lesions and benign (class 2) lesions. But as the set of suspicious lesions was enlarged with the same type of lesions, a linear binary classifier was found not to perform satisfactorily, motivating the development and use of clustering, which is used to obtain discrimination between class 1 and class 2 lesions through the identification of one set of class 1 clusters and another set of class 2 clusters, each cluster comprising a certain number of independent measurements.…”
Section: Clusteringmentioning
confidence: 99%
See 4 more Smart Citations
“…Preliminary results based on analyses of independent measurements performed on a limited set of suspicious lesions [15,16] indicated that a linear binary classifier would suffice to discriminate between independent measurements on malignant (class 1) lesions and benign (class 2) lesions. But as the set of suspicious lesions was enlarged with the same type of lesions, a linear binary classifier was found not to perform satisfactorily, motivating the development and use of clustering, which is used to obtain discrimination between class 1 and class 2 lesions through the identification of one set of class 1 clusters and another set of class 2 clusters, each cluster comprising a certain number of independent measurements.…”
Section: Clusteringmentioning
confidence: 99%
“…In two previous studies [15,16], the application of optical transfer diagnosis (OTD) for noninvasive detection of skin cancer was discussed, the objective being to evaluate the potential of this technology for differentiation of benign from malignant pigmented melanocytic lesions. After scanning, lesions were biopsied for histopathologic examination, each by two separate dermatopathologists.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations